Evaluation of the effectiveness of a bioremediation process in experimental soils polluted with chromium and lindane - Aparicio, Juan Daniel (2019)
Bioremediation using actinobacterium consortia proved to be a promising alternative for the purification of co-contaminated environments. In this sense, the quadruple consortium composed of Streptomyces sp. M7, MC1, A5, and Amycolatopsis tucumanensis AB0 has been able to remove significant levels of Cr(VI) and lindane from anthropogenically contaminated soils. However, the effectiveness of the bioremediation process could not be evaluated only by analytical monitoring, which is complex mainly due to the characteristics of the matrix, producing non-quantitative analyte recoveries, or interferences in the detection stage and quantification. However, the effectiveness of the bioremediation process cannot be evaluated only through analytical monitoring, which is complex due mainly to the characteristics of the matrix, to the recoveries of non-quantitative analytes or to interferences in the detection and quantification stage. For this reason, it is essential to have tools of ecological relevance to assess the biological impact of pollutants on the environment. In this context, the objective of this work was to establish the appropriate bioassays to evaluate the effectiveness of a bioremediation process of co-contaminated soils. For this, five model species were studied: four plant species (Lactuca sativa, Raphanus sativus, Lycopersicon esculentum, and Zea mays) and one animal species (Eisenia fetida). On plant species, the biomarkers evaluated were inhibition of germination (IG) and the length of hypocotyls/steam and radicles/roots of the seedling. While on E. fetida, mortality (M), weight lost, coelomocyte concentration and cell viability were tested. These bioindicators and the battery of biomarkers quantified in them showed a different level of sensitivity, from maximum to minimum: E. fetida > L. esculentum > L. sativa > R. sativus ≫> Z. mays. Therefore, E. fetida and L. esculentum and their respective biomarkers were selected to evaluate the effectiveness of the bioremediation process due to the capability of assessing the effect on the flora and the fauna of the soil, respectively. The joint application of these bioindicators in a field scale bioremediation process is a feasible tool to demonstrate the recovery of the quality and health of the soil.